1996
DOI: 10.1007/s001340050213
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility in aerobic gram-negative bacilli isolated in intensive care units in 39 French teaching hospitals (ICU study)

Abstract: Rates of resistance in AGNB as a whole and in particular species (P. aeruginosa, Klebsiella), as well as frequency of concomitant resistance found in the French ICU study, were higher than those found in ICU studies conducted with the same methodology in Belgium, The Netherlands, and Germany, which may reflect differences in case mix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 0 publications
5
29
0
1
Order By: Relevance
“…Similar findings were reported in a Belgian study [21]. The rank order of bacterial species was also comparable to that reported for ICUs in French teaching hospitals [8]. The distribution of gram-negative bacteria in ICUs in eight Turkish hospitals was also similar, except that the positions of Enterobacter spp.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar findings were reported in a Belgian study [21]. The rank order of bacterial species was also comparable to that reported for ICUs in French teaching hospitals [8]. The distribution of gram-negative bacteria in ICUs in eight Turkish hospitals was also similar, except that the positions of Enterobacter spp.…”
Section: Discussionsupporting
confidence: 88%
“…The European Prevalence of Infection in Intensive Care Units (EPIC) study involving hospitals from 17 countries showed large differences in the prevalence of infections and the mortality rate in ICUs [7]. Furthermore, the susceptibility of pathogens to antimicrobial agents varies both over time and between countries, although data are often limited to aerobic gram-negative bacilli [8,9,10,11] or address only enterococci [12,13]. Only a few studies have addressed resistance in both gram-negative and gram-positive bacteria from patients in ICUs [14].…”
Section: Introductionmentioning
confidence: 99%
“…Focusing more specifically on antibiotic resistance, the EPIC data reveals that antibiotic resistance occurs frequently among organisms causing infection in ICU patients, a fact supported by other studies within Europe [12,13,14,15,16,17,18,19] and worldwide [20,21,22,23]. It is clear that the resistance of organisms to antibiotics is increasing [16,24], and resistance rates are particularly high in the ICU.…”
Section: Antimicrobial Resistancementioning
confidence: 71%
“…CA-ASB comprises a large reservoir of antimicrobial-resistant organisms, particularly on critical care units, and can be the source of cross-infection [31,[58][59][60][61][62][63]. One study reported that 15% of episodes of hospital-acquired bacteriuria occur in clusters [58], and these often involve highly antimicrobial-resistant organisms.…”
Section: Introductionmentioning
confidence: 99%